Family Resilience and Children's Subjective Well-Being: A Two-Wave Study - Andreja Brajša-Žganec; Marija Džida; Maja Kućar (MDPI AG, 2024)
According to the Theory of Change, the resilience of the family unit plays a crucial role in shaping the developmental trajectory of children. Families exhibiting higher levels of family resilience are typically characterized by transparent and effective communication, optimistic outlooks on adversity, adept problem-solving skills, strong spiritual beliefs, and effective management of social and financial resources. While existing research has indicated that parental and familial characteristics can predict diverse outcomes for children, investigations concerning the association between family resilience and children's subjective well-being remains limited. Therefore, this study aims to examine whether different dimensions of family resilience can predict changes in children's subjective well-being, tested one year later. The sample includes 762 child-mother-father triads (intact families). Children aged 9-13 years (48% boys, age = 11.04, SD = 1.16) assessed their life satisfaction, positive and negative affect in two study waves, while mothers and fathers assessed family resilience in the first wave. A dyadic data common fate model was employed to create latent variables representing family resilience. Three latent variables were: family problem-solving, family spirituality, and utilization of social and economic resources. Findings from the structural equation model indicated a positive association between higher levels of family problem-solving and increased children's life satisfaction, alongside a negative relationship between higher family spirituality and negative affect. Parental assessments of social and economic resources utilization were not uniquely related to children's life satisfaction, positive, or negative affect.